Effect of ultraviolet light irradiation on the growth of Candida albicans and the transversal strength of acrylic plate - Widodo, Teguh Tri; Ardan, Rachman; Prijono, Eddy (Universitas Padjadjaran, 2010)
Introduction: Acrylic plates are the basis for several tools used in the oral cavity, including dentures and obturators. In its function, the acrylic plate is always in contact with the oral mucosa, so that good disinfection is needed without reducing the strength of the acrylic plate. Disinfection can be done by ultraviolet irradiation. This study is aimed to analyze the effect of ultraviolet light irraying on the growth of Candida albicans and the strength of transversal acrylic plate. Methods: This research is an experimental laboratory research with Replication Random Design. The disinfection success test was carried out by observing the population of the Candida albicans colony, while the acrylic plate transversal strength test was carried out on 35 acrylic heat curing plates tested according to ADA specifications. Results: Ultraviolet light can inhibit the growth of Candida albicans colonies with an optimum irradiation time of 20 minutes at a wavelength of 254nm. Meanwhile, ultraviolet irradiation on acrylic plates between 5-30 minutes shows a significant transverse strength. Conclusion: Ultraviolet light at appropriate wavelengths and times has been shown to significantly inhibit bacterial colony growth and significantly increase the transverse strength of acrylic plates.